Forming a Resilient Personality The Importance of Character Education in the Modern Era - Misriandi; Susanto, Ahmad (Global Synthesis in Education Journal, 2024)
This study investigates the impact of physical activity on the social skills of elementary school students in South Tangerang. Utilizing a factor analysis approach, the research examines various dimensions of physical activity—including frequency, duration, and type—and their correlations with key social competencies such as communication, teamwork, empathy, and conflict resolution. A sample of 164 students from ten elementary schools in South Tangerang was selected through stratified random sampling to ensure representativeness. Data were collected using validated questionnaires and observational assessments conducted over six months. Statistical analysis revealed that regular participation in structured physical activities significantly enhances students' social skills, with team-based sports showing the most substantial positive effects. Additionally, the study identified specific factors within physical activity programs that contribute to developing social competencies, including cooperative gameplay, leadership opportunities, and inclusive participation strategies. These findings suggest that integrating comprehensive physical activity programs into the elementary school curriculum can foster essential social skills, thereby contributing to students' overall personal and academic development. The study recommends that educators and policymakers prioritize implementing and supporting diverse physical activity initiatives to promote a holistic educational environment. Future research should explore the long-term effects of sustained physical activity on social skills and investigate the potential moderating variables such as socioeconomic status and cultural background.